Phenotypic and functional characterization of synovial fluid-derived fibroblast-like synoviocytes in rheumatoid arthritis - Ditte Køster (Nature Portfolio, 2021)
Abstract Fibroblast-like synoviocytes (FLS) play an important pathological role in persistent inflammatory joint diseases such as rheumatoid arthritis (RA). These cells have primarily been characterized in the RA synovial membrane. Here we aim to phenotypically and functionally characterize cultured synovial fluid-derived FLS (sfRA-FLS). Paired peripheral blood mononuclear cells (PBMC) and sfRA-FLS from patients with RA were obtained and monocultures of sfRA-FLS and autologous co-cultures of sfRA-FLS and PBMC were established. The in situ activated sfRA-FLS were CD34-, CD45-, Podoplanin+, Thymocyte differentiation antigen-1+. SfRA-FLS expressed uniform levels of NFкB-related pathway proteins and secreted several pro-inflammatory cytokines dominated by IL-6 and MCP-1. In a co-culture model with autologous PBMC, the ICAM-1 and HLA-DR expression on sfRA-FLS and secretion of IL-1β, IL-6, and MCP-1 increased. In vivo, human sfRA-FLS were cartilage invasive both at ipsilateral and contralateral implantation site. We conclude that, sfRA-FLS closely resemble the pathological sublining layer FLS subset in terms of surface protein expression, cytokine production and leukocyte cross-talk potential. Further, sfRA-FLS are comparable to tissue-derived FLS in their capabilities to invade cartilage at implantation sites but also spread tissue destruction to a distant site. Collectively, sfRA-FLS can serve as a an easy-to-obtain source of pathological sublining FLS in RA.